2017
DOI: 10.1038/s41598-017-10497-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Molecular Mechanism of the Subcellular Localization and Cell-to-cell Movement of the Sugarcane mosaic virus P3N-PIPO

Abstract: The coding sequence of P3N-PIPO was cloned by fusion PCR from Sugarcane mosaic virus (SCMV), a main causal agent of sugarcane (Saccharum spp. hybrid) mosaic disease. SCMV P3N-PIPO preferentially localized to the plasma membrane (PM) compared with the plasmodesmata (PD), as demonstrated by transient expression and plasmolysis assays in the leaf epidermal cells of Nicotiana benthamiana. The subcellular localization of the P3N-PIPO mutants P3N-PIPOT1 and P3N-PIPOT2 with 29 and 63 amino acids deleted from the C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…The distribution of P3N-PIPO under the condition of TuMV infection was also analyzed with the same strategy. Consistent with previous studies (16,20), P3N-PIPO-YFP was located mainly on the plasma membrane, which also contained PDs in the cells infected with TuMV-6K2mCh (Fig. 4E).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The distribution of P3N-PIPO under the condition of TuMV infection was also analyzed with the same strategy. Consistent with previous studies (16,20), P3N-PIPO-YFP was located mainly on the plasma membrane, which also contained PDs in the cells infected with TuMV-6K2mCh (Fig. 4E).…”
Section: Resultssupporting
confidence: 92%
“…P3N-PIPO functions in cell-to-cell movement by interacting with CI and targeting it to the PD (16). Moreover, a study on Sugarcane mosaic virus (SCMV) showed that P3N-PIPO interacts with both CI and PCaP1 via its C-terminal PIPO domain (20). BiFC assays showed that TuMV CI also interacts with P3N-PIPO via the PIPO domain (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering that TuMV is synergistic with Cucumber mosaic virus (CMV) and promotes the cell‐to‐cell movement of the transport‐deficient isolate CMV‐Y (Takeshita & Takanami, ), we speculate that PD actin filament depolymerisation may contribute to this synergism. The homologues of PCaP1 not only interact with the P3N‐PIPO of TuMV (Vijayapalani et al ., ) but also those of Tobacco vein banding mosaic virus (Geng et al ., ) or Sugarcane mosaic virus (Cheng et al ., ), which implicates a general requirement for PCaP1 in potyviral cell‐to‐cell movement. However, TuMV eventually establishes systemic infection in pcap1 (Vijayapalani et al ., ) or P PCaP1 :PCaP1 N5A ; pcap1 in the present work, indicating that PCaP1 may be involved in the early stage of TuMV infection, or other actin filament‐severing proteins are involved in TuMV infection.…”
Section: Discussionmentioning
confidence: 77%
“…Further movement of VRC to cell periphery and PD requires a nonconventional pathway bypassing ER-Golgi trafficking and involving VTI11, a pre-vacuolar compartment SNARE protein [84] . P3N-PIPO, which binds to VRC through P3-P3N interactions [72] , is a critical component of VRC vesicles specifically required for the PD targeting, and the PD association of P3N-PIPO depends on the PIPO domain [85] .…”
Section: Potyvirusesmentioning
confidence: 99%